Comparative performances of soluble urokinase plasminogen activator receptor and Mid-regional proADM to predict composite death and new heart failure rehospitalisation in acutely breathless patients. (3rd October 2022) - Chew-Harris, J; Kuan, W S; Ibrahim, I; Chan, S P; Li, Z; Liew, O W; Appleby, S; Frampton, C; Troughton, R; Chong, J P C; Tan, L L; Lin, W; et al.
Abstract: Background: Soluble urokinase plasminogen activator receptor (suPAR) is a pleotropic receptor, capable of orchestrating plaque vulnerability and vascular immune dysfunction. Mid-regional pro-adrenomedullin (MR-proADM) is the stable peptide precursor of adrenomedullin, with concentrations reflective of vasodilation and cardiac remodelling. We compared the prognostic performances of suPAR and MR-proADM for the composite clinical endpoint of death and new heart failure (HF) in patients with undifferentiated breathlessness. Methods: Patients presenting to hospital with the primary complaint of acute dyspnoea were recruited in New Zealand (n=612) and in Singapore (n=483)]. Baseline plasma measurements were undertaken for suPAR (ViroGates) and MR-proADM (Thermo Scientific). Cardiac biomarker levels of NT-proBNP (Roche) was available on all patients. Statistical assessment was made using SPSS v28 (IBM), with all biomarkers treated as continuous variables and presented as median [interquartile range (IQR)]. Prognostic performance of suPAR, MR-proADM and NT-proBNP to predict the composite clinical endpoint of death/new HF at 90-days and 1-yr were assessed using receiver operator curve (ROC) area under the curve (AUC) analysis (Z-scores) and Cox hazard regression analysis (per doubling of biomarker concentrations) after adjustment for traditional risk factors. P-value <0.05 was considered statistically significant. Results: In the entire acutely breathless cohort [median age: 65 years (IQR: 52.9–76.0), 63.1% males], 343/1095 of patients had the final adjudication of ADHF. suPAR and MR-proADM concentrations were higher with increasing age (Spearmans rho, r>0.46, P<0.0001), lower eGFR (r>0.58, P<0.0001) and in those with ADHF (r>0.40, P<0.0001). During the follow-up period, 122 patients were categorised with death/new HF by 90-days, rising to 281 at 1-year. suPAR and MR-proADM were able to predict death/new HF at 90-days (both ROC-AUC >0.77) and at 1-year (both ROC-AUC ≥0.78) (Table 1). All markers were however less accurate in predicting this endpoint in the presence of ADHF (ROC-AUC <0.71). After adjustment in Cox-regression modelling, suPAR obtained HR >1.35 per doubling of suPAR concentrations (P=0.001) for outcomes at 90-days and at 1-year (Table 2), achieving the highest prognostic performance for this clinical endpoint, followed by NT-proBNP (HR >1.29) (Table 2), whilst MR-proADM was not an independent predictor of death/HF in this cohort. suPAR was also an independent predictor of death/HF for patients with ADHF, obtaining HR >1.35 per doubling of concentrations. Above a cut-off concentration of 3.6 ng/mL, suPAR was associated with a HR of 2.1 (95% CI: 1.55–2.91) for death/HF at 1-year for acutely dyspnoeic patients. Conclusion: suPAR concentrations is superior than MR-proADM in predicting the clinical end-point of death/HF at 1-year in this cohort. It may aid in risk-stratification strategies for the management of acutely breathless patients. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): National Heart Foundation of New ZealandHealth Research Council of New Zealand